Osteosarcoma with Pulmonary Metastasis in a German Shepherd Dog - Betala, Baby Manasa; Kodali, Nagesh Babu; Paidi, Mohini Kumari; Maddireddy, Himaja; Lam, Ratnakumari; Rednam, Amarendhra Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Osteosarcoma is the most common bone tumor in the dogs with highest incidence among bone neoplasms and exhibits aggressive behaviour characterized by both local invasiveness and distant metastases (Cavalcanti et al., 2004; Withrow and Vail, 2007). Osteosarcoma can arise in any bone of appendicular skeleton, in the following order of frequency: humerus, radius, ulna, femur, and tibia (Liu et al., 1977). Osteosarcoma is a highly metastatic neoplasia, mainly towards the lungs, with 90% of the animals developing metastases within one year after limb amputation (Brodey and Riser, 1969). Some breeds like Doberman Pinscher, Saint Bernard, German Shepherd, Golden Retriever, Great Dane and Irish Setter are described as having an increased risk of developing osteosarcoma (McNeill et al., 2007; Morello et al., 2010). The present paper describes appendicular osteosarcoma with metastasis of lungs in 12 year old German shepherd dog.